Pilot Survey of Fuel Consumption in Rural Areas - IV - Sagar, S. R.; Chandola, L. P.; Ansari, M. Y. (Indian Forester, 1985)
A pilot survey of fuel consumption in rural areas was conducted by the Forest Economics Branch of Forest Research Institute & Colleges in 1974 in the following regions : Region I - Villages surrounded by the Forests - Chakrata; Region II - villages near the Forests - Harrawala; Region III - Villages away from the Forests - Karaundi. The results of these surveys have been reported in two papers (1976) and (1981). The present survey conducted in 1983 was done to study the changes in three localities. The Comparison of the Survey show that: 1. There is a tendency to go towards agriculture; 2. Size of the family is increasing; 3. Dungeake consumption is decreasing. Villages in the third region as indicated by Karaundi population are going for Eucalyptus plantation.